Kajian Nilai-Nilai Pendidikan Akhlak dalam Film Animasi Hafiz dan Hafizah - Arifani Amril; Aep Saepudin; Heru Pratikno (Bandung Conference Series: Islamic Education, 2024)
Abstract. Education is a process of transferring knowledge from people who know to people who don't know (students). Moral education is a conscious effort to guide and direct a person's will to achieve noble behavior and make it a habit. Moral education is very important in developing human potential, so it is necessary to instill educational values in students. The family is the main educator for children, therefore parents have the responsibility to educate children. One of parents' efforts to instill moral educational values is to provide shows that are not just entertainment but also provide teaching. The existence of the animated film Hafiz and Hafizah overcomes parents' concerns so that it continues to provide educational viewing which includes scenes containing moral educational values. The formulation of the problem in the research is: (a). What are the values of moral education in the animated film Hafiz and Hafizah? (b). What is the meaning of the moral values represented in the animated film Hafiz and Hafizah? (c). What is the content of the moral message in the animated film Hafiz and Hafizah? The objects of research in this film are the animation of Hafiz and Hafizah in the episodes Amanah A Wallet, Cleanliness Is Part of Faith, Hafiz Hiccups, Assalamualaikum Friends, I Want To Be, A Surprise for Dad. This research is library research with primary data sources, namely the Hafiz and Hafizah animation films, while secondary data sources include books, journals, etc. Which relates to the values of Islamic education. Researchers use documentation techniques in collecting data, as well as using data analysis techniques, namely content analysis. Based on the research results from the five episodes taken, it was found that the meaning of the moral values contained in the animated film Hafiz and Hafizah Abstrak. Pendidikan merupakan proses transfer pengetahuan dari orang yang tahu kepada orang yang belum tahu (peserta didik). Pendidikan akhlak adalah usaha yang dilakukan secara sadar untuk membimbing dan mengarahkan kehendak seseorang untuk mencapai tingkah laku yang mulia dan menjadikannya sebagai kebiasaan. Pendidikan akhlak sangat penting dalam pengembangan potensi manusia, sehingga perlu ditanamkan nilai-nilai pendidikan kepada peserta didik. Keluarga merupakan pendidik yang utama bagi anak, oleh sebab itu orang tua memiliki tanggung jawab dalam mendidik anak. Salah satu upaya orang tua dalam menanamkan nilai-nilai pendidikan akhlak yaitu memberikan tontonan yang bukan hanya sekedar hiburan tetapi juga memberikan pengajaran. Adanya film Animasi Hafiz dan Hafizah mengatasi keresahan orang tua agar tetap memberikan tontonan yang mendidik yang didalamnya menampilkan adegan yang berisi nilai-nilai pendidikan Akhlak. Rumusan masalah dalam penelitian yaitu : (a). Apa saja nilai- nilai pendidikan akhlak dalam film animasi Hafiz dan Hafizah? (b). Bagaimana makna nilai-nilai akhlak yang direpresentasikan dalam film animasi Hafiz dan Hafizah? (c). Bagaimana isi pesan akhlak dalam film animasi Hafiz dan Hafizah?. Objek penelitian dalam film ini yaitu Animasi Hafiz dan Hafizah episode Amanah Sebuah Dompet, Kebersihan Sebagian dari Iman, Hafiz Cegukan, Assalamualaikum Sahabat, Aku Ingin Menjadi, Kejutan Untuk Ayah. Penelitian ini merupakan penelitian kepustakaan (Library research) dengan sumber data primer yaitu film Animasi Hafiz dan hafizah, sedangkan sumber data sekunder berupa buku-buku, jurnal,dll. Yang berkaitan dengan nilai-nilai pendidikan Islam. Peneliti menggunakan teknik dokumentasi dalam pengumpulan data, serta menggunakan teknik analisis data yaitu content analysis(analisis isi). Berdasarkan hasil penelitian dari lima episode yang diambil ditemukan makna nilai- nilai akhlak yang terdapat dalam film animasi Hafiz dan Hafizah